Association of breast arterial calcification and carotid atherosclerosis as a marker of cardiovascular risk - E. V. Bochkareva; E. K. Butina; N. Kh. Bayramkulova; I. V. Kim; O. V. Molchanova; E. M. Filichkina; E. B. Yarovaya; V. A. Metelskaya; O. M. Drapkina (Столичная издательская компания, 2023)
Aim. To study the relationship between breast arterial calcification (BAC) and the presence and severity of carotid atherosclerosis.Material and methods. We analyzed 4274 digital mammograms of women who underwent diagnostic mammography. In addition to the standard diagnosis of breast diseases, BAC was assessed in all mammograms. The study included 198 women aged 40-74 years, who made up 2 groups with and without BAC, each consisting of 99 people, formed on a case-control basis. The severity of BAC was assessed by a 12-point score. Duplex ultrasound of extracranial arteries determined plaque presence, the severity of CA stenosis (in percent) and intima-media thickness (IMT). All women underwent physical and laboratory examinations, electrocardiography, and were interviewed using a questionnaire assessing socio-demographic data, menopausal status, risk factors, and diseases.Results. The groups did not differ in lipid levels, blood glucose, body mass index, incidence of hypertension, diabetes, or smoking. Women with BAC had a higher incidence of menopause (94,9% vs 84,8%, p=0,033), coronary artery disease (13,1% vs 4,2%, p=0,039) and osteoporosis (18,2% vs 6,1%, p=0,016) in       history. In women with BAC, at least one carotid plaque was observed significantly more often than in those without BAC - in 79,8% and 60,6% of cases, respectively (p=0,005). Women with BAC compared with women without BAC had a greater plaque number (1,0 [1,0; 3,0] vs, 1,0 [1,0; 2,0], p<0,001) and a more severe carotid stenosis, assessed by maximum (25,0 [17,5; 35,0] vs 20,0 [0,0; 27,5], p=0,001), total (30,0 [20,0; 92,5] vs 25,0 [0,0; 50,0], p<0,001) and mean arterial stenosis (25,0 [17,5; 30,0] vs 20,0 [0,0; 25,0], p=0,001). For the first time, a positive relationship was revealed between the severity of carotid atherosclerosis and BAC as follows: women with greater severity of maximum and total carotid stenosis had more severe BAC (p=0,018 and p=0,003, respectively). There was no association between BAC and IMT (p=0,115).Conclusion. BAC is associated with a higher incidence and severity of carotid atheromatosis. A positive relationship was found between the severity of BAC and carotid stenosis. The data obtained confirm the prospects of mammography as a screening technique for identifying individuals with an increased cardiovascular risk.